2015
DOI: 10.1097/hjh.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of baroreflex activation therapy on arterial stiffness and central hemodynamics in patients with resistant hypertension

Abstract: Apart from peripheral blood pressure, baroreflex activation therapy reduces central blood pressure, augmentation index at a heart rate of 75 b.p.m. and pulse wave velocity in patients with resistant hypertension, suggesting strong potential to reduce cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 28 publications
0
29
1
1
Order By: Relevance
“…For BAT, the Barostim neo (CVRx, Minneapolis, MN) was used as described previously. [15][16][17] The BAT device consists of a lead, which is sutured directly on 1-side carotid sinus and a pulse generator implanted in an infraclavicular position in a minimal invasive procedure, including intraoperative testing for optimal placement of the lead for BP response. Thereafter, BAT was initiated 4 weeks after implantation and the stimulation was individually increased by adaption of programmed parameters (pulse amplitude [1-20 mA], pulse width [15-500 ms] and frequency 10-100 pulses/s) during monthly follow-up according to patients' office BP and tolerance.…”
Section: Patients Bat and Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…For BAT, the Barostim neo (CVRx, Minneapolis, MN) was used as described previously. [15][16][17] The BAT device consists of a lead, which is sutured directly on 1-side carotid sinus and a pulse generator implanted in an infraclavicular position in a minimal invasive procedure, including intraoperative testing for optimal placement of the lead for BP response. Thereafter, BAT was initiated 4 weeks after implantation and the stimulation was individually increased by adaption of programmed parameters (pulse amplitude [1-20 mA], pulse width [15-500 ms] and frequency 10-100 pulses/s) during monthly follow-up according to patients' office BP and tolerance.…”
Section: Patients Bat and Study Protocolmentioning
confidence: 99%
“…Thereafter, BAT was initiated 4 weeks after implantation and the stimulation was individually increased by adaption of programmed parameters (pulse amplitude [1-20 mA], pulse width [15-500 ms] and frequency 10-100 pulses/s) during monthly follow-up according to patients' office BP and tolerance. Follow-up data were acquired as described before [15][16][17] 6 months after starting BAT.…”
Section: Patients Bat and Study Protocolmentioning
confidence: 99%
“…Although sympathetic nerve overactivity is predictive for survival and cardiovascular events in patients with ESRD [12], improvement of such endpoints by BAT remains to be shown. However, in previous trials, beneficial effects of BAT were prospectively demonstrated on glucose metabolism [35], vascular stiffness [35] and proteinuria [36]. Minor side-effects associated with slight discomfort occurred frequently in our patients.…”
Section: Discussionmentioning
confidence: 83%
“…Third, we acknowledge that the follow-up period of 2 years is relatively short for cardiovascular outcome parameters. Our study was designed to study the effect of vitamin B12 and folic acid supplementation on PWV, and for this parameter, a 2-year intervention is considered to be sufficient, because PWV is known to respond quickly as other trials with PWV as outcome variable have shown [8,29,30]. Nevertheless, arterial stiffness is known for its limited reversibility and therefore it cannot be ruled out that differences in PWV levels may have been detected when using a longer intervention period.…”
Section: Discussionmentioning
confidence: 98%